The impacts of product recall of halal products - Siti Zamanira Mat Zaib; Azila Jaini; Zaminor Zamzamir@Zamzamin; Nor Hafiza Othman; Zurina Shafii (Faculty of Entrepreneurship and Business,UMK, 2015)
Halal product is complying with Islamic principles in syariah law. It is demanding by the customers due to the concept of halal and thoyyib (clean) in its processing. Halal product is not only for Muslim, but also for all people in the world including non-Muslim. Many customers demand for halal product because of confidence level during the processing from farm to fork which contribute positive impacts to the company. However, there are some problems with the products that might be recalled from the market place which give significant impact to the performance of the company. Thus, this paper aims to explore the impacts of product recall of Halal products to the manufacturers and the approaches used by the company to recover negative impacts to the company. Lastly, the result showed that the company initiated several aspects to improve Halal policy management to recover customers’ confidence, image and loss of costs.